After 3D Printing, What's Next: Discovering Scientific Trends of 4D Printing - Ventayen, Randy Joy M. (Future Science / FSH-PH Publications, 2024)
he field of additive manufacturing has seen the rise of 3D Printing and 4D Printing as noteworthy subjects of research. This study highlights the advancements in advanced Printing techniques. To identify, evaluate, and analyze the existing literature on this subject, the research followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, focusing on documents indexed in the Elsevier Scopus database. Through bibliometric analysis (BA), including co-authorship, keyword co-occurrence, and citations, the research landscape and scientific progress in this area were examined. The analysis revealed that a total of 1,638 documents have been published and indexed on this topic since its inception. The search was conducted on February 17, 2023, at 2:30 AM +8 GMT. The results indicated that articles are the primary form of publication, with a strong emphasis on Materials Science, Engineering, and Chemistry as the favored thematic subjects in the published works. Among the various sources of publications, ACS Applied Materials and Interfaces, published by ACS Publications, emerged as the most influential. On the research leadership front, Gladman A. Sydney, affiliated with Harvard University, was identified as the most influential lead researcher in this domain. Further examination revealed that prolific authors in this field are primarily associated with institutions in China, the United States, India, the United Kingdom, and Singapore. In conclusion, the findings highlight that the trend of 4D Printing within the scientific community is still in a phase of ongoing development.